3D validation, 2D feasibility, corrected and developed correlations for pure solid-gallium phase change modeling by enthalpy-porosity methodology. (May 2023) - Ye, Wei-Biao; Arıcı, Müslüm
Abstract: Literature survey found that three important scientific problems including: i ) The feasibility of 2D modeling was not be further validated by compared the 3D & 2D simulations with the famous classic experiments of literature; In literature's work, ii ) the plus exponent of the aspect ratio in liquid-fraction correlation is questionable, and iii ) how to calculate the Mean Liquid Layer Thickness ( l c ) was not mentioned and/or discussed that would lead to get the value of l c -based Nusselt number difficultly. Therefore, in this work, the 3D validation and 2D feasibility are roundly reported as compared by all the experimental data of literature. The novel results and core findings in the paper are that: i ) It is confirmed that the present 3D simulation on pure gallium melting by enthalpy-porosity technique is completely validated, and 3D simulation can be replaced by 2D one, and it also should be replaced by 2D due to high running time ratio nearly from 17 to 27 times depended powerfully on the aspect ratio of computational domain; Thereinto, ii ) the sign of the aspect-ratio exponent shown in the correlation equation of Liquid fraction vs. Stefan number of literature is clarified and corrected, and iii ) the correlation of l c is now well-proposed to calculate the l c -based Nusselt number directly and quickly, and then the developed l c 's correlation is commented from multi-points of views. Finally, the discrepancy sources between current 3D & 2D modeling and literature's experimental measuring on the pure solid‑gallium phase change are discussed and summarized in detail. It should be mentioned that the currently obtained new results and novel findings will promote the new understandings and high efficiency applications in related fields, e.g., transient cooling of high heat-flux electronic devices in aerospace and navigation that would be researched in the future. Highlights: Validate 3D enthalpy-porosity modeling pure gallium melting completely. Illuminate feasibility on 3D simulation replaced by 2D simplification strictly. Correct aspect-ratio exponent in literature's liquid-fraction correlation as negative. Develop correlation of mean liquid layer thickness to calculate Nusselt number.